2013
DOI: 10.1002/ajh.23446
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of JAK2V617F mutation by next‐generation sequencing technology

Abstract: response in PV with limited toxicity [1]. The ability of Pegasys to induce complete molecular responses suggests selective targeting of the malignant clone [2]. Earlier clinical studies have likewise demonstrated a beneficial effect in early stage B-CLL using nonpegylated interferon alpha 2a [3]. The diagnosis of concomitant CLL/MPN is a rare event and in a recent study analysis of prognostic markers for CLL demonstrated that in patients with a coexistent MPN, lymphoproliferative disorders follow a clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…To obtain very high coverage (i.e., approximately 2 million reads per sample), 24 samples were analyzed per run. Bioinformatic analysis was performed as described in our previous work [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…To obtain very high coverage (i.e., approximately 2 million reads per sample), 24 samples were analyzed per run. Bioinformatic analysis was performed as described in our previous work [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, NGS has become more widely available and although these platforms may not currently be suited for the detection and/or quantitation of MPN‐associated mutations in all diagnostic laboratories, the feasibility and accuracy of these methods have already been established in MPN molecular diagnostics: targeted exome sequencing allows the identification of several mutations that have prognostic significance with identification of these mutations demonstrated to be of clinical value in predicting relapse in the post‐ASCT setting . With improvements in sensitivity, targeted NGS of specific MPN‐associated mutations may also afford the detection of residual disease and leukaemic transformation . Development and implementation of both commercial and in‐house NGS‐based assays for the detection of MPN‐associated mutations will require both inter‐ and intralaboratory evaluation of ongoing performance with preliminary studies addressing these issues achieving high concordance .…”
Section: Future Directionsmentioning
confidence: 99%
“…184,185,197 Abdelhamid et al demonstrated in a proof-of-principle study robust detection of JAK2 V617F in PB by HTS with high concordance to qPCR, even at low AFs. 199 Lundberg et al applied a targeted HTS panel (104 genes) to serial blood samples and showed that the number of emergent mutations over time was low, characterizing these diseases as genetically stable. This study also illustrated the capability of HTS to detect the expansion of preexisting clones harboring TP53 and TET2 mutations toward transformation to AML.…”
Section: Chronic Myeloid Leukemiamentioning
confidence: 99%